Prevalence of Xerostomia in Patients Referred to Shiraz Dental School, Shiraz, Iran during 2006-2013 - Jannan GHAPANCHI; Fahimeh REZAZADEH; Erfan FAKHRAEE; Aisa ZAMANI (Tehran University of Medical Sciences, 2016)
Prevalence of Xerostomia in Patients Referred to Shiraz Dental School, Shiraz, Iran during 2006-2013